The Cognitive Information Effect of Televised News - Lăzăroiu, George; Pera, Aurel; Ştefănescu-Mihăilă, Ramona O.; Bratu, Sofia; Mircică, Nela (Frontiers in Psychology, 2017)
ABSTRACT. The purpose of this review is to summarize the key findings which prove that the biased perceptions of viewers may provide an inaccurate image of the informational validity of televised news. The news may generate distorted recollections of what occurred in particular reported events if displayed routines influence viewers not to pay attention to the essential features of a narrative. Elaborating on Gunter (2015), Zelizer (2010), and Fiske and Hartley (2010), we indicate that the character of the news setting has altered and individuals’ news consumption routines have changed in adapting to media advancements. The news may be undergone at various psychological stages by news publics. Televised news may transmit information undeviatingly to publics that may (not) be committed successfully to memory. Our paper shows that individuals’ skills to handle information that is displayed in a linguistic configuration are influenced by their abilities in the utilization of certain symbol systems that are employed to represent notions and meanings. Televised news may shape what individuals grasp, influence their perceptions, convictions, and views regarding prevailing events and matters, and transmit knowledge and interpretation. If news stories can be jotted down in a linguistic style that sidesteps making needless processing demands and captivate news users by facilitating them to make connections with former knowledge, they may be more worthy of note and more edifying. We conclude that news narratives present a cognitive demanding task to individuals, displaying novel information regarding evolving events in a multifarious format. Broadcast news exhibits intricate contents, displaying configurations that employ excessively the cognitive abilities for information processing of viewers.